Choice of Allograft in Patients Requiring Intestinal Transplantation: A Critical Review. (3rd May 2017) - Huard, Genevieve; Schiano, Thomas; Moon, Jang; Iyer, Kishore
Abstract : Intestinal transplantation (ITx) is indicated in patients with irreversible intestinal failure (IF) and life-threatening complications related to total parenteral nutrition (TPN). ITx can be classified into three main types. Isolated intestinal transplantation (IITx), that is, transplantation of the jejunoileum, is indicated in patients with preserved liver function. Combined liver-intestine transplantation (L-ITx), that is, transplantation of the liver and the jejunoileum, is indicated in patients with liver failure related to TPN. Thus, patients with cirrhosis or advanced fibrosis should receive a combined allograft, while patients with lower grades of liver fibrosis can usually safely undergo ITx. Reflecting their degree of sickness, the waitlist mortality rate and the early posttransplant outcomes of patients receiving L-ITx are worse than IITx. However, L-ITx is associated with better long-term graft and patient survival. Multivisceral transplantation (MVTx), that is, transplantation of the organs dependent on the celiac axis and superior mesenteric artery, can be classified into full MVTx if it includes the liver and modified MVTx if it does not. The most common indications for MVTx are extensive portomesenteric thrombosis and diffuse gastrointestinal pathology such as motility disorders and polyposis syndrome. Every patient with IF should undergo a multidisciplinary evaluation by an experienced ITx team.